2017
DOI: 10.1002/jcb.25993
|View full text |Cite
|
Sign up to set email alerts
|

HX‐1171, a Novel Nrf2 Activator, Induces NQO1 and HMOX1 Expression

Abstract: HX-1171 (1-O-hexyl-2,3,5-trimethylhydroquinone) is a novel synthesized vitamin E derivative, which reportedly has positive effects on various diseases and conditions, such as liver fibrosis, hepatic cirrhosis, and cancer. In this study, we analyzed the transcriptional activity induced by HX-1171. Results from reverse transcription polymerase chain reaction and promoter assays reveal that HX-1171 increased the expression of NQO1 and HMOX1, encoding antioxidant-related enzymes, in A549 human lung epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The observed increase in HMOX1 expression induced by CP-312 was greater and more rapid compared with CDDO-Me or CoPP, which induce HMOX1 by activating Nrf2 pathway via inhibition of keap1 interaction with Nrf2. In addition to HMOX1, NQO1 is a prototypical target gene of Nrf2 (Kumar et al, 2011;Kim et al, 2017). Differences in the dynamics of the HMOX1 response and the lack of NQO1 upregulation in hiPSC-CMs treated with CP-312 lead us to speculate that CP-312 may be regulating HMOX1 expression in a Nrf2independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The observed increase in HMOX1 expression induced by CP-312 was greater and more rapid compared with CDDO-Me or CoPP, which induce HMOX1 by activating Nrf2 pathway via inhibition of keap1 interaction with Nrf2. In addition to HMOX1, NQO1 is a prototypical target gene of Nrf2 (Kumar et al, 2011;Kim et al, 2017). Differences in the dynamics of the HMOX1 response and the lack of NQO1 upregulation in hiPSC-CMs treated with CP-312 lead us to speculate that CP-312 may be regulating HMOX1 expression in a Nrf2independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we discovered a new Nrf2 activator, HX-1171. HX-1171 showed superiority in increasing the expression of Nrf2 target genes compared to tBHQ, another Nrf2 activator, and a remarkable effect in promoting nuclear translocation of Nrf2 [ 29 ]. Thus, we investigated the efficacy of HX-1171 in an STZ-induced diabetic model to confirm whether HX-1171 could be effective for diabetic conditions like other Nrf2 activators.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, genetic Nrf2 induction significantly reduced beta cell damage in the reactive oxygen species (ROS)-mediated mouse model of diabetes, whereas genetic Nrf2 deficiency resulting from conditional-Nrf2 knockout markedly aggravated beta cell damage [ 28 ]. Therefore, we investigated the antidiabetic effect of HX-1171, a newly discovered Nrf2 activator [ 29 ], in the INS-1 pancreatic beta cell line and the STZ-induced diabetic mouse model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BTT‐105 (1‐O‐hexyl‐2,3,5‐trimethylhydroquinone), a hydroquinone derivative, is a potent anti‐oxidant and anti‐fibrotic small molecule 2–6 . BTT‐105 showed that increased anti‐oxidant defense genes through increasing the nuclear erythroid 2‐related factor 2 (Nrf2) 7 . BTT‐105 finished Phase I study, and showed well tolerability and safety in normal healthy subjects up to 2000 mg/day 8…”
Section: Introductionmentioning
confidence: 99%